Properties of aqueous solutions of triblock copolymers of ethylene oxide and propylene oxide and their mixtures with surfactants studied by surface tension and neutron reflection - Viera, J; Josélio, Vieira (2002)
﻿ The adsorption and the aggregation behaviour of poly(ethylene oxide-b-propylene oxide- b-ethylene oxide) copolymers (EPE) and their mixtures with surfactants of different ionic characters: sodium dodecyl sulphate (SDS), dodecyltrimethylammonium chloride (DTAC) and tetraethylene glycol monooctyl ether (C8E4), have been investigated using surface tension and neutron reflection measurements. The first part of the thesis is concerned with the adsorption properties of EPE copolymers at the air-solution interface. The surface tension curves for the copolymers show two breaks similar to those published for Pluronic 3 surfactants (commercially available EPE copolymers). Earlier explanations of this behaviour are inconsistent with the neutron reflection results. The adsorption isotherms obtained by neutron reflection have two steps, one at low concentrations leading to a plateau followed by a substantial rise up to the CMC. The low-concentration breakpoint is attributed to two different effects, the depletion of copolymer molecules in the bulk of the solution and the composition polydispersity. In general, the structure of the adsorbed layer can be described in terms of four layers. The outermost layer is always water free and contains only PO units. The EO residues form tails, which extend into the solution over a distance shorter than the fully extended length. Depending on the conditions, some PO is also found in this tail region. The second part of the thesis is concerned with the effect of mixing EPE copolymers with surfactants of different ionic characters. The formation of mixed micelles and mono layer between EPE 3000-14 and ionic surfactants show a surprisingly strong attractive interaction, which is attributed to a dehydration mechanism. In the mixed micelle formation, in particular, the loss of hydration water molecules found in the micelle core of the copolymer would lead to a substantial gain in entropy. The surface compositions from neutron reflection generally disagree with the predictions of Pseudophase Separation Model. It is believed that changes of hydration upon mixing may be responsible for the deviations as it is not taken into account by the Pseudophase Separation Model. From the neutron reflection studies, DTAC appears to accumulate preferably in the uppermost part of the mixed interfacial layer, while SDS would rather stay in the aqueous phase region. In the C8E4/EPE 3000-14 system, the mixed micellization results in strong repulsive interaction, which is attributed to a further hydration of the copolymer micelle core by the incorporation of the solvated C8E4 headgroups. However at the air-solution interface, both C8E4 and EPE 3000-14 are found to mix ideally. The difference between mixed micelle and mono layer formation observed for such a system is believed to be associated with the structure of the two states. The orientation of the copolymer molecules in the interfacial layer is such that the contact of PO groups with water molecules is significantly reduced. C8E4 molecules appeared to adsorb preferentially within the uppermost part of the interfacial layer rich in PO groups.